Comparison Of Ginger Decoction And Fresh Lemon Juice In Reducing Emesis Gravidarum Among First-Trimester Pregnant Women - Annisa Namirah Nasution; Yulia Fatma nasution Fatma nasution; Dilla Kurnia (Universitas Satya Terra Bhinneka, 2026)
Background: Emesis gravidarum commonly affects women during the first trimester and may impair nutritional status and quality of life. Ginger and lemon are widely used as complementary therapies, although comparative evidence remains limited. Objective: To compare the effectiveness of standardized ginger decoction and fresh lemon juice in reducing emesis gravidarum. Methods: A quasi-experimental pretest-posttest two-group study was conducted among 30 first-trimester pregnant women at an independent midwifery practice in Medan, Indonesia. Participants received either ginger decoction (n = 15) or fresh lemon juice (n = 15) once daily for four consecutive days. Emesis severity was assessed using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE-24) questionnaire. Results: Both interventions significantly reduced PUQE scores (p < 0.001). The reduction was greater in the ginger group (5.60 points) than in the lemon group (3.87 points) (p < 0.001). Conclusion: Both therapies effectively reduced emesis gravidarum, with ginger decoction demonstrating superior clinical effectiveness and greater potential as a complementary therapy during early pregnancy.